Carga laboral de los trabajadores de la empresa Servientrega Vinces - Macias Gonzalez, Genaro Omar (2019)
The present investigation describes how the workload can affect people in many ways, including mental and physical health, as well as discomfort in jobs to such a degree of fatigue. This work helps us as future administrators, managers to be more aware of our employees know their concerns, weaknesses supervise their work so that as a team they can meet the goals set within an organization. The purpose of this work was to know how the Serv bellyga Vinces agency developed internally with respect to the work overload that was occurring in the collaborators of this institution, so it was of great importance, knowledge, and a great experience to share directly with the people affected and try to raise awareness about what is right or wrong in their workplaces